Calcipotriol/betamethasone dipropionate aerosol foam for the treatment of psoriasis vulgaris: a review of real-world evidence (RWE). (17th November 2021) - Gerdes, Sascha; Velasco, Manuel; Wu, Jashin J.; Hubo, Mario; Veverka, Karen A.
Abstract: Background: Randomized controlled trials (RCTs) demonstrated the advantages of an aerosol foam formulation of calcipotriol/betamethasone dipropionate (Cal/BD) in patients with psoriasis. In this review, we investigated whether such benefits could also be obtained in real-world clinical practice. Methods: PubMed was searched for studies reporting real-world data in patients with psoriasis treated with Cal/BD aerosol foam. Results: Three large real-world studies with Cal/BD aerosol foam were identified: a prospective non-interventional study from Germany, a medical chart review from the US, and a retrospective non-interventional study from Spain. Some key findings included the following: high levels of adherence to treatment (82–93%); after 4 weeks, about 50% of patients achieved complete/almost complete responses; at final assessment, 85–95% of patients were extremely satisfied/very satisfied/satisfied with Cal/BD aerosol foam; all healthcare providers were satisfied or somewhat satisfied with the efficacy of Cal/BD foam and they reported similar findings for symptom improvements (itch, pain, erythema/redness, flaking, and plaque thickness). Global ratings by investigators/healthcare providers for symptom control, overall efficacy and the emotional status of patients were also very high (75–100%). Conclusion: The results from real-world studies undertaken in diverse healthcare systems reinforce the positive findings reported in RCTs with Cal/BD aerosol foam in patients with psoriasis.